2020
DOI: 10.1080/23748834.2020.1788322
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and biodiversity loss in the post-COVID-19 era: complex challenges and possible solutions

Abstract: Although biodiversity conservation and restoration can significantly contribute to environmental health in urban areas, rapid urbanization undermines biodiversity in various ways. We hypothesize that one challenge that will arise after the COVID-19 pandemic is the accelerated expansion of urban areas through two distinct mechanisms: more informal settlements due to increased poverty and increased urban sprawl due to increased suburban development. In response to this challenge, we call for a global agenda to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…58,59 Overall, this strong evidence suggests that abnormalities in kidney health may be an early warning in identifying the impact of changes in the planetary health on overall human health. Finally, the social and economic consequences of the pandemic 60,61 are likely to further impact the availability and allocation of resources for healthcare, setting up a vicious cycle.…”
Section: One Healthmentioning
confidence: 99%
“…58,59 Overall, this strong evidence suggests that abnormalities in kidney health may be an early warning in identifying the impact of changes in the planetary health on overall human health. Finally, the social and economic consequences of the pandemic 60,61 are likely to further impact the availability and allocation of resources for healthcare, setting up a vicious cycle.…”
Section: One Healthmentioning
confidence: 99%
“…Lennon [ 12 ] articulated this view, noting that issues of form and features, distribution, connectivity and resilience within planning are of paramount importance to our responses to Covid-19. Rastandeh and Jarchow [ 13 ] go further, outlining a program of action that places nature and enhanced ecological resources at the center of change. Both papers argue that issues of distribution and equity in spatial planning are complex and that any reaction to Covid-19 needs to take into account the scope of the ecological, economic and social factors influencing urban functionality and health.…”
Section: Introductionmentioning
confidence: 99%
“…Pohl, 2022: 712). Noting the differential access enjoyed by wealthier suburbanites to green space, imagination of the desertified pandemic inner city suggested that post-COVID urban planning needs to insert accessible wildlife-supportive and vibrant green spaces in the heart of our cities (see Rastandeh and Jarchow, 2021).…”
Section: New Urban Lives and Lifestylesmentioning
confidence: 99%